Lipid kinases PIP5K7 and PIP5K9 are required for polyamine‐triggered K+ efflux in Arabidopsis roots. (19th August 2020) - Zarza, Xavier; Van Wijk, Ringo; Shabala, Lana; Hunkeler, Anna; Lefebvre, Matthew; Rodriguez‐Villalón, Antia; Shabala, Sergey; Tiburcio, Antonio F.; Heilmann, Ingo; Munnik, Teun
SUMMARY: Polyamines, such as putrescine, spermidine and spermine (Spm), are low‐molecular‐weight polycationic molecules present in all living organisms. Despite their implication in plant cellular processes, little is known about their molecular mode of action. Here, we demonstrate that polyamines trigger a rapid increase in the regulatory membrane lipid phosphatidylinositol 4, 5‐bisphosphate (PIP2 ), and that this increase is required for polyamine effects on K + efflux in Arabidopsis roots. Using in vivo 32 Pi ‐labelling of Arabidopsis seedlings, low physiological (μm ) concentrations of Spm were found to promote a rapid PIP2 increase in roots that was time‐ and dose‐dependent. Confocal imaging of a genetically encoded PIP2 biosensor revealed that this increase was triggered at the plasma membrane. Differential 32 Pi ‐labelling suggested that the increase in PIP2 was generated through activation of phosphatidylinositol 4‐phosphate 5‐kinase (PIP5K) activity rather than inhibition of a phospholipase C or PIP2 5‐phosphatase activity. Systematic analysis of transfer DNA insertion mutants identified PIP5K7 and PIP5K9 as the main candidates involved in the Spm‐induced PIP2 response. Using non‐invasive microelectrode ion flux estimation, we discovered that the Spm‐triggered K + efflux response was strongly reduced in pip5k7 pip5k9 seedlings. Together, our results provide biochemical and genetic evidence for a physiological role of PIP2 in polyamine‐mediated signalling controlling K + flux in plants. Significance Statement: Polyamines, such as putrescine, spermidine and spermine, are low‐molecular‐weight polycations present in all living organisms. Despite their involvement in various plant cellular processes, little is known about their molecular mode of action. Here, we demonstrate that polyamines trigger a rapid increase in the signalling lipid PIP2 at the plasma membrane of Arabidopsis roots by activating two lipid kinases, PIP5K7 and PIP5K9, and that this lipid response is required for the K + efflux that is triggered downstream.